(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2024)
Abstract The study aims to clarify the impact of the adoption of the International Financial Reporting Standard (IFRS16) on lease contracts in the General Iraqi Insurance Company on the financial statements, and thus the impact on financial ratios and indicators, Since the financial reporting standard considers lease contracts as an asset called the right to use the asset and is offset by a liability, this changes the way the financial statements are presented, with an addition to both the asset and liability sides. In order to show the extent to which the adoption of the standard reflects on the financial performance of the company, new accounts were added in accordance with the requirements of applying the IFRS16 standard,The researchers reached a set of conclusions, most notably that the adoption of IFRS16 in insurance companies plays a major role in enhancing the quality of financial reporting and disclosure, which naturally indicates the quality of accounting information. This reflection has also affected financial ratios and indicators, Based on the above, the researchers proposed several recommendations, the most important of which is the adoption of the International Financial Reporting Standard (IFRS16) on lease contracts in Iraqi insurance companies, in compliance with the current trends in adopting international standards, on the one hand, and keeping pace with the latest developments taking place globally, on the other hand, as insurance companies have dealings with global counterparties.